Linking Functional Traits To Trophic Roles In Scavenger Assemblages - Violeta Marie Montenegro; Patricia Mateo‐Tomás; Jessica Schneider; Daisy H. Dent; Tom Crowther; Carolina Bello (Ecology and Evolution)
ABSTRACT Scavenging is a widespread feeding strategy involving a diversity of taxa from different trophic levels, from apex predators to obligate scavengers. Scavenger species play a crucial role in ecosystem functioning by removing carcasses, recycling nutrients and preventing disease spread. Understanding the trophic roles of scavenger species can help identify specialized species with unique roles and species that may be more vulnerable to ecological changes. To identify species with specialized roles, we studied three scavenger networks (one in north temperate Spain and two in central‐south Mediterranean Spain) that comprised 25 scavenger species (65% birds and 35% mammals), consuming carcasses of four wild ungulate species. We characterized the trophic role of a species by combining four species‐level network metrics (normalized degree, specialization, closeness, and betweenness centrality) into a single centrality metric, quantifying how scavenger species interact with carcass species within their ecological network. Higher centrality indicates the species feeds on a greater variety of carcasses and may contribute more to carrion consumption than species with lower centrality, which have more peripheral and specialized roles. The griffon vulture (Gyps fulvus) and the azure‐winged magpie (Cyanopica cyanus) had the highest centrality. In contrast, the red kite (Milvus milvus) in the northern site had the lowest centrality, and the Egyptian vulture (Neophron percnopterus) was among the most peripheral species for all three networks. In general, scavengers with large home ranges and nocturnal or crepuscular activity patterns tended to have more central roles, whereas species that forage silently tended to have more peripheral roles. Changes in species' centrality between sites and the high centrality of species with large home ranges suggest that management strategies in one location can have implications that extend beyond, highlighting the need to implement coordinated transboundary protection efforts to ensure the resilience and functionality of scavenger networks and derived ecosystem services.